2016
DOI: 10.5194/angeo-34-751-2016
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of International Reference Ionosphere electron density in the polar cap and cusp using EISCAT Svalbard radar measurements

Abstract: Abstract. Incoherent scatter radar measurements are an important source for studies of ionospheric plasma parameters. In this paper the EISCAT Svalbard radar (ESR) long-term database is used to evaluate the International Reference Ionosphere (IRI) model. The ESR started operations in 1996, and the accumulated database up to 2012 thus covers 16 years, giving an overview of the ionosphere in the polar cap and cusp during more than one solar cycle. Data from ESR can be used to obtain information about primary pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…In Themens and Jayachandran [2016], it was demonstrated that the IRI performs poorly in representing total electron content (TEC) in the polar cap, auroral oval, and subauroral regions, particularly during the equinoxes at high solar activity. These issues at high solar activity were also confirmed via incoherent scatter radar (ISR) observations by Bjoland et al [2016]. Themens et al [2014] showed that the IRI produces significant errors in its representation of the F 2 peak of THEMENS ET AL.…”
Section: Introductionmentioning
confidence: 75%
“…In Themens and Jayachandran [2016], it was demonstrated that the IRI performs poorly in representing total electron content (TEC) in the polar cap, auroral oval, and subauroral regions, particularly during the equinoxes at high solar activity. These issues at high solar activity were also confirmed via incoherent scatter radar (ISR) observations by Bjoland et al [2016]. Themens et al [2014] showed that the IRI produces significant errors in its representation of the F 2 peak of THEMENS ET AL.…”
Section: Introductionmentioning
confidence: 75%
“…Themens and Jayachandran () show that the errors in the IRI‐generated topside thickness account for the majority of the errors in the IRI's representation of high‐latitude TEC. These errors were further verified by incoherent scatter radar (ISR) observations at several polar cap and auroral oval locations (Bjoland et al, ; Themens, Jayachandran, & Varney, ), where Themens, Jayachandran, and Varney () relate these errors to several different limitations in the current NeQuick parameterization. In the subauroral trough region, Xiong et al () showed that the IRI overestimates near peak and lower topside electron density by an average of 20%.…”
Section: Introductionmentioning
confidence: 81%
“…(2009). The satellite Ionospheric Pierce Points (IPPs) were estimated at an altitude of 350 km as it is believed that most of the high‐latitude scintillations are caused by irregularities at the F region peak altitude (Basu et al., 1978; Bjo˙land et al., 2016), although the production of scintillation at a lower altitude cannot be ruled out (Deshpande et al., 2016). The amplitude scintillation index ( S 4 ) is computed according to the following expression: S4=SI2SI2SI2, where SI is the signal intensity.…”
Section: Chain and Data Reductionmentioning
confidence: 99%